Antioxidant properties of rubus discolor l. extracts and protective effects of its flower extract against hydrogen peroxide-induced oxidative stress in wistar rats - Keser, Serhat; Celik, Sait; Turkoglu, Semra; Yilmaz, Ökke; Turkoglu, Ismail (Turkish Pharmacists Association, 2015)
In the present study, in vitro antioxidant activities of ethanol and water extracts of Rubus discolor L. leaves, flower, unripe and ripe fruits were investigated. Additionally, the antioxidant and protective properties of R. discolor flower (RD) water extract on some important biochemical parameters against hydrogen peroxide (HP)-induced oxidative stress in rats were determined. The phytochemical profiles and antioxidant properties (scavenging against DPPH•, ABTS•+, H2O2, O2-, metal chelating, inhibition of lipid peroxidation and reducing power) of extracts were determined by spectrophotometric methods and HPLC. The antioxidant potential of RD flower extract supplementations were evaluated by measuring total protein, glutathione (GSH), malondialdehyde (MDA), vitamin A and E, cholesterol, glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) levels in various tissues. The flower extracts were the most active extracts for in vitro antioxidant assays. In HP administered groups, MDA level was increased, GSH and total protein levels were decreased. In RD treated group, these substances levels were protected. In RD plus HP treated group, SOD and GSH-Px levels were increased. These results show that RD flower extract have the protective effects against H2O2 via its free radical scavenging activity, and this extract affected the level of antioxidant enzymes, vitamin A and E, cholesterol, GSH, total protein and MDA. © 2015, Turkish Pharmacists Association. All rights reserved.
Rubus discolor L. ekstrelerinin antioksidan özellikleri ve çiçek ekstresinin hidrojen peroksit-nedenli oksidatif stres Oluşturulmuş wistar sıçanlarda koruyucu etkileri
Keywords: Cholesterol; GSH; Hydrogen peroxide; MDA; Rubus discolor; SOD